Synthesis of nanostructured CO3O4 as anode materials for lithium-ion batteries - Liu, Shuhui. (2009)
Cobalt oxide (Co3O4) nanostructures were synthesized by a simple surfactant-assisted hydrothermal method. The influence of reaction parameters such as reaction time, different cobalt precursors, the molar ratio of starting materials, and amounts of surfactant added, on the size and morphology of the final samples was investigated via several characterization technqiues. X-ray diffraction (XRD) demonstrated that the products were pure face-centred cubic Co3O4. Scanning electron microscopy (SEM) revealed different morphologies of the final Co3O4 particles – cubic, spherical and hexagonal particles, scaffold-like structures, nanoflakes and nanowires as a result of variation of the different reaction parameters. Transmission electron microscopy (TEM) revealed the dimensions of the Co3O4 particles.